Rancang Bangun Prototype Sistem Pendeteksi Kebocoran Gas dan Api Menggunakan Arduino - Retno Waluyo; Dani Khoirul Wafa; Zulia Karini; Ito Setiawan (Infotekmesin, 2020)
The Indonesian government conducted a household fuel conversion program in 2007 using LPG as a substitute for kerosene. LPG gas is the most widely used energy source for the people of Indonesia. Currently the quality of LPG gas cylinders tends to decrease. This quality degradation can occur due to lack of supervision during the production process, especially in the quality control process, so the use of LPG is quite dangerous with the potential to cause an explosion to fire. The aim of this research is to design and build a prototype of a gas and fire leak detection system using Arduino. The method used in this research is the prototype development method with the stages of listening to problems and customer needs, building a prototype, then the customer sees the prototype and tests it. The results of this study are tools that can detect LPG and fire gas leaks using an arduino microcontroller that can be accessed using a smartphone with an average response time to detect a fire of 4.43 seconds while to detect a gas of 4.18 seconds.